Strategi Pengembangan Potensi Wisata dalam Meningkatkan Minat Wisatawan pada Pantai Cemare Lombok Barat: Tourism Potential Development Strategy in Increasing Tourist Interest in Cemare Beach, West Lombok - Kamaludin; Vidya Yanti Utami; Dhea Candra Dewi; Nidya Putri Syahida (JURNAL EKONOMI, BISNIS DAN PARIWISATA, 2025)
Cemare Beach is a beach located in Cemare Hamlet, South Lembar District. This beach has considerabletourism potential to be developed as a tourist attraction. The purpose of this research is to describe thepotential and analyze the strengths, weaknesses, opportunities and threats contained in Cemare Lembarbeach so that the right tourism attraction potential development strategy can be determined. This researchuses qualitative descriptive analysis techniques. Primary data was obtained through direct observation to theresearch location and interviews with relevant informants, while secondary data was obtained by conductingliterature studies using references to several journals that are in accordance with the topic. The data was thenanalyzed using the SWOT matrix method. The results revealed that the strategy to develop the tourismpotential of Cemare Beach can be done by (1) Conducting promotions (2) Improving infrastructure andtourist facilities (3) Collaborating with the Regency and Provincial governments, various stakeholders (4)Adding water sports tours (5) Showcasing cultural arts and local seafood culinary specialties of CemareBeach (6) Disaster mitigation and (7) Maintaining and preserving the environment. The development strategythat has been prepared is expected to be able to become a reference to develop the potential of Cemare Beachtourism objects.